Climate Impacts on Fire Risk in Desert Shrublands: A Modeling Study - Moloney, Kirk A.; Fuentes-Ramirez, Andres; Holzapfel, Claus (Frontiers in Ecology and Evolution, 2021)
Fire is recognized to be an important disturbance in many ecosystems worldwide, although desert ecosystems are not generally thought of as being prone to fire, primarily because of the lack of a continuous fuel bed. However, the likelihood of catastrophic fires in some desert systems is increasing due to the spread of exotic species, which can grow in the open. A second factor increasing fire risk may be extreme rainfall events caused by climate warming that can lead to an increase in fuel loads. Our work explores the impact of increased rainfall on fire risk in creosote shrublands that have been invaded by exotic grasses. We take experimental results from creosote (Larrea tridentata) shrublands in the Mojave and Sonoran Deserts of the Southwestern United States and develop spatially explicit simulation models to explore the impact of shifting rainfall regimes on biomass production and fire spread. In doing this, we explore two scales that are important in the spread of fire: 1) the macro-scale which considers the likelihood that fire arriving at one edge of a modeled landscape will successfully reach the opposite edge, leading to spread at a broader scale and 2) the micro-scale, which considers fire spread within the landscape. We use a very simple model to first explore how changes in the distribution of fuel in the landscape impact the ability of fire to spread across and within the landscape. We then add more realism by including a direct consideration of creosote shrub distributions and biomass levels produced in different vegetation zones associated with distance from creosote. Our models show that the spread of fire at both macro- and micro-scales can be predicted from a knowledge of the statistical distribution of biomass in the field. The only additional information that is needed to predict the extent of fire spread is the amount of biomass at a local site (g m-2) required to ignite standing biomass in adjacent sites. This will depend upon species composition as well as amount of biomass, the hydration status of the vegetation and climatic conditions, such as windspeed and relative humidity.